2022
DOI: 10.1007/s11069-022-05546-x
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of different forecasting tools for short-range lightning strike risk assessment

Abstract: Thunderstorms, the main generator of lightning on earth, are characterized by the presence of extreme atmospheric conditions (turbulence, hail, heavy rain, wind shear, etc.). Consequently, the atmospheric conditions associated with this kind of phenomenon (in particular the strike itself) can be dangerous for aviation. This study focuses on the estimation of the lightning strike risk induced by thunderstorms over the sea, in a short-range forecast, from 0 to 24 h. In this framework, three methods have been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Ground-based networks have been employed since the 1950s to detect lightning (Bouchard et al 2023). The National Lightning Detection Network TM (hereafter NLDN), operated by Vaisala, Inc. (Orville 2008) and the Earth Networks Total Lightning Network ® (hereafter ENTLN), operated by Earth Networks, Incorporated (Liu and Heckman 2011) are two major ground-based systems used in North America.…”
Section: Lightning Detection Networkmentioning
confidence: 99%
“…Ground-based networks have been employed since the 1950s to detect lightning (Bouchard et al 2023). The National Lightning Detection Network TM (hereafter NLDN), operated by Vaisala, Inc. (Orville 2008) and the Earth Networks Total Lightning Network ® (hereafter ENTLN), operated by Earth Networks, Incorporated (Liu and Heckman 2011) are two major ground-based systems used in North America.…”
Section: Lightning Detection Networkmentioning
confidence: 99%
“…It is found that the main activity center of lightning is related to the supercooled cloud layer, and the negative charge area of cloudto-ground lightning is mainly located in the temperature level of −5 to −25 °C (Bouchard et al, 2023). Considering that 40-dBZ echo intensity at the height of −10 °C can be used as the best factor to predict the occurrence of the first lightning, Maribel analyzed several convective cells and found that the condition for lightning in the cell is that the top height of the echo above 40 dBZ in the cell must be higher than 7 km.…”
Section: The Echo Intensity Thresholdmentioning
confidence: 99%